Oral condition of critical patients and its correlation with ventilator-associated pneumonia: a pilot study - Andrea Carvalho De Marco; Camila Galvão Cardoso; Fernando Vinicius Cesar De Marco; Antonio Braulino de Melo Filho; Mauro Pedrine Santamaria; Maria Aparecida Neves Jardini
INTRODUCTION: Literature has reported inadequate oral hygiene conditions in Intensive Care Unit (ICU) patients and the occurrence of Ventilator-associated pneumonia in about 9%-27% of all intubated patients. OBJECTIVE: The aim of this study was to evaluate ICU patient's oral conditions and correlate this with the presence of ventilator-associated pneumonia. MATERIAL AND METHOD: Twenty-three patients were categorized in the following way: with periodontal disease and ventilator-associated pneumonia, with periodontal disease and without ventilator-associated pneumonia, without periodontal disease and with ventilator-associated pneumonia, and with neither periodontal disease nor ventilator-associated pneumonia. The periodontal disease index, plaque index, and decay-missing-filled index were used in the assessment. RESULT: There was no statistically significant difference in the incidence of periodontal disease with respect to ventilator-associated pneumonia, but the number of teeth and surfaces with attachment loss above 4 mm was always greater in patients with ventilator-associated pneumonia. CONCLUSION: The extent of periodontal disease may contribute to the onset of ventilator-associated pneumonia. However, studies with a larger sample are needed to validate this relationship.